POSESSION AND OWNERSHIP OF LAND RIGHTS AS OBJECTS IN LAND PROCUREMENT PROGRAME (THE DIGNIFIED JUSTICE PERSPECTIVE) - Teguh Prasetyo; Jeferson Kameo (Surakarta Law and Society Journal, 2019)
In the Indonesian land law, individual right of lands are subject to the public interest. A right of land must have a social function. Nowadays, this policy is taking the form in the Land Procurement Act. One therefore could argue that the legal basic of a compulsory land procurement policy is stronger at the meantime, compare to the one before. Aspects which are regulated in the Law, among other things are the mandatory purchase procedures of land purchasing; the price of the land and these further schedulled in the generally Government regulations. The price of the land is prescribed one- sided by the Government as the purchaserwhois the party in the government contract, representing or acting on behalf of the State. This law has been long recognized in the Indonesian legal system. There are several types of Government compulsory purchases of land rights. The first category is a purchasing of a land right from the temporary holder and the second category is the compulsory purchase of an ownership of land from the permanent holder. In this article, this principle will be briefly examined. For this purpose, the writers use a homegrown but internationally recognised legal philosophy called as Dignified Justice Theory or Philosophy.